Chinese Lexical Semantics 14th Workshop, CLSW 2013, Zhengzhou, China, May 10-12, 2013. Revised Selected Papers - Liu, Pengyuan; Su, Qi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed selected papers from the 14th Chinese Lexical Semantics Workshop, CLSW 2013, held in Zhengzhou, China, in May 2013. The 68 full papers and 4 short papers presented in this volume were carefully reviewed and selected from 153 submissions. They are organized in topical sections covering all major topics of lexical semantics; lexical resources; corpus linguistics; and applications on natural language processing.
Lexical semantics -- Lexical resources -- Corpus linguistics -- Applications on natural language processing.
Keywords: Computer science; Artificial intelligence; Translators (Computer programs).; Chinese language; Computer Science; Artificial Intelligence (incl. Robotics).; Language Translation and Linguistics; Chinese